Investigating The Drivers of Cost and Schedule Performance in Ghana's Road Construction (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
ABSTRACTPurpose: This study investigates the extent of contract cost and timeline overruns in Ghana’s road construction sector by analysing historical data from feeder road projects. It seeks to determine whether project type, size, and duration influence cost and schedule overruns.Design/Methodology/Approach: The study employs a quantitative research approach using archival data. A census sampling technique was used to select 156 feeder road projects in Northern Ghana based on the availability of reliable data. Projects from 2019 to 2020 were chosen due to consistent documentation and to avoid political bias, ensuring a sufficient sample for statistical analysis. This approach enhanced the study’s reliability and the applicability of its findings on cost and time overruns.Findings: The findings confirm that cost and schedule overruns vary significantly across project types, sizes, and durations. Routine maintenance projects exhibited minimal overruns, whereas bitumen surfacing and rehabilitation projects experienced substantial cost and timeline overruns. Larger and longer-duration projects had higher overruns compared to smaller and shorter-term projects.Research Limitation: The study focuses on feeder road projects within a specific geographic region and timeframe, limiting the generalizability of its findings to other construction sectors. Future research should examine a broader range of projects and include qualitative insights into the causes of overruns.Practical Implication: The study provides empirical evidence that can guide policymakers, contractors, and project managers in implementing measures to reduce cost and timeline overruns.Social Implication: Addressing cost and time overruns can lead to better resource allocation and timely project completion, benefiting local communities and stakeholders.Originality/Value: The introduction of project typology as a performance factor, along with the suggestion of contractor classification as a future variable, adds originality and depth.
Keywords: Construction. cost overrun. delay. projects. road